On two new species of the genus Ctenolepisma (Zygentoma: Lepismatidae) from India - Hazra, Ashis Kumar; Jana, Debanjan; Mandal, Guru Pada; Molero-Baltanás, Rafael (Zootaxa, 2022)
Two new species of the genus Ctenolepisma Escherich, 1905 are described from Andhra Pradesh and Tamil Nadu, India: Ctenolepisma (Ctenolepisma) venkataramani sp. n. and Ctenolepisma (Ctenolepisma) udumalpetense sp. n. Their affinities with related species are discussed and a key to the Indian species of the genus is provided.